2004
DOI: 10.1007/s00441-004-0897-3
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis of transportation pathways of microspheres after their introduction into the uterine horn cavity in cyclic pigs

Abstract: Countercurrent transfer is thought to be one of the most important mechanisms involved in the transfer of substances between the uterus and oviduct. The present study was aimed at recognizing other putative transportation pathways from the uterine cavity through the oviduct onto the surface of and into internal ovarian structures. Microspheres (latex beads, 0.8 microm in diameter) were introduced into the uterine horn cavity of pigs, for 30 min, at various days of the estrous cycle. The transportation pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Recently, it has been demonstrated that microspheres 0.8 μ m in diameter introduced into the lumen of the uterine horn in sows reached the ovary and corpora lutea through the lumen of the oviduct (Doboszyńska and Andronowska 2004). These results suggest that prostaglandins produced in the uterus may also use this pathway.…”
Section: Destination Of Pgf2α Transfer From the Uterus To The Ovarymentioning
confidence: 99%
“…Recently, it has been demonstrated that microspheres 0.8 μ m in diameter introduced into the lumen of the uterine horn in sows reached the ovary and corpora lutea through the lumen of the oviduct (Doboszyńska and Andronowska 2004). These results suggest that prostaglandins produced in the uterus may also use this pathway.…”
Section: Destination Of Pgf2α Transfer From the Uterus To The Ovarymentioning
confidence: 99%